ANALISIS CUSTOMER RELATIONSHIP MANAGEMENT DAN SERVICE QUALITY TERHADAP CUSTOMER VALUE MELALUI CUSTOMER SATISFACTION PADA BANK PEMERINTAH DI SURABAYA - Kusnadi, A.M. (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2010)
The aim of this study was to know and analyze : (1) Influence of customer relationship management  on Customer Satisfaction, (2) Influence of customer management on Customer Value , (3) Influence of service quality on Customer Satisfaction , (4) Influence of service quality on customer value, (5) Influence of Customer Satisfaction  on Customer Value , (6) Influences of customer relationship management  and service quality on Customer Value  through Customer Satisfaction, (7) Influence of customer relationship management  on Customer Value  through Customer Satisfaction , (8) Influence of service quality on customer value through customer satisfaction, (9) Influence of service quality  on customer relationship management .            The population in this study involved all customers of  current account, saving, and time deposit in Surabaya, with minimum criteria of 3 (three) months being  customers. Accidental sampling technique was used in this research and 400 customers were obtained. Structural equation modeling (SEM) was used  as analysis technique  by using AMOS 4.01 software.            The result of this study showed that customer analysis management and service quality provided significant influences on customer value through Customer Satisfaction in state banks in Surabaya  Keywords:  Customer    relationship    management,    service    quality,    Customer Satisfaction ,  value.